(untitled) (Nuntius Antiquus, 2010)
The aim of the present paper is analysing the strategy of embedding erotic and fantastic short narratives in Petronius’ Satyricon and in Apuleius’ Metamorphoseon. The function of those stories of magic and seduction in narrative composition, it is propposed, is a way of keeping the readers’ attention to the central story, although it deviates from it directly.